Impact of vertical loading on the implant‐bone interface. Issue 8 (24th April 2012) - Mehl, Christian; Becker, Stephan T.; Acil, Yahya; Harder, Sönke; Wiltfang, Jörg; Dabbagh‐Afrouz, Arthur A.; de Buhr, Wiebke; Kern, Matthias
Abstract Objectives The main aim of this study was to evaluate the impact of vertical loading occurring during removal of cemented restorations on the implant‐bone interface. Methods Thirty‐six titanium implants (Camlog 4.3 × 9 mm) were placed 1 mm supraosseous in the frontal skull of four minipigs. After a 13 week healing period the implants were exposed and the implant stability was measured. Three implants per minipig were vertically loaded using 20 or 100 impulses, respectively with an 18 Ns impulse imitating a crown removal. Three implants were left unloaded as control. The animals were sacrificed after 13 or 18 weeks. The harvested specimens were analyzed using scanning electron microscopy (SEM), light and fluorescence microscopy. Results No post operative complications or deaths of the minipigs occurred. All implants osseointegrated. The average bone‐implant contact area (BIC) was 78 ± 5.1%. No statistically significant difference could be found when comparing the BIC areas of the control and the experimental groups between the sacrificed animals at 13 weeks and 18 weeks (P > 0.05). Therefore, the results of each subgroup were pooled. No significant differences regarding the BIC area could be detected between the control and the experimental groups (P > 0.05). Except one failing implant no cracks due to vertical loading could be evaluated in the SEM. Fluorescence microscopy revealed a significantly higher bone remodeling activity in the vertically loaded groups. Conclusions Removal of cemented implant restorations seems not to have an impact on the mechanical implant stability, but seems to increase bone remodeling activity.